December 2024 (Avocetta, 2025)
This column aims to collect a series of interesting observations, collected without time, space or species limitation, focusing on a limited series of category of interest.In this volume of Avocetta, you will find news items about the following species: Common Merganser (Mergus merganser), White Stork (Ciconia ciconia), Eurasian Stone-curlew (Burhinus oedicnemus), Black Tern (Chlidonias niger), Barn Owl (Tyto alba), Short-eared Owl (Asio flammeus), Pallid Harrier (Circus macrourus), Monk Parakeet (Myiopsitta monachus)/Yellow-legged Gull (Larus michahellis), Zitting Cisticola (Cisticola juncidis), House Martin (Delichon urbicum)/Barn Swallow (Hirundo rustica), Isabelline Wheatear (Oenanthe isabellina).